Factors Impacting the Remaining Income of Village Unit Cooperative - Lestari Rahayu Waluyati; Jamhari Jamhari; Abi Pratiwa Siregar; Dewi Meitasari; Anila Indrianti Anggraini; Ikrimah Nur Hanifah; Dian Ari Ramadhani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2022)
Cooperatives have different characteristics and goals from profit-oriented entities (Investor-Owned Firms (IOFs)). Nevertheless, obtaining income higher than the costs incurred (surplus) is one of the efforts that can be made to maintain the sustainability of the business unit and the cooperative organization itself. Based on these conditions, this study aims to determine the factors that affect the remaining income. The type of data used in this study is secondary data obtained from cooperative stakeholders. The objective of this study has been answered by using multiple regression analysis with the common effect model. The independent variables consist of the number of members, own capital, and external capital. Furthermore, based on data analysis, it can be concluded that of the three exogenous variables, only own capital and external capital has a significant effect, and both have a positive impact. The findings of this study strengthen the strategic role of reserve fund allocation and other efforts to increase own capital to support organizational and business development. On the other hand, the increase in external capital needs to be watched carefully. Although it helps increase the remaining income, this type of capital has financial burden consequences